STRATEGI GURU AL-QUR’AN HADITS DALAM MENINGKATKAN HAFALAN JUZ AMMA (AN-NAS– AL-FIIL) SISWA KELAS VII DI MTS YASNAM SAMUSTIDA KECAMATAN TELUK KERAMAT - Mona Mona (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2016)
The purpose of this study is to find out about: 1) To find out the strategies of the teacher of the Qur'an Hadith in improving the memorization of Juz Amma class VII students at MTs Yasnam Samustida. 2) To find out the steps of the teacher of the Qur'an Hadith in improving the memorization of Juz Amma class VII students at MTs Yasnam Samustida. 3) To know and understand the supporting and inhibitory factors in memorizing the Qur'an of class VII students at MTs Yasnam Samustida. To obtain data related to the focus of the study, researchers conduct interviews, observations and documentation using cameras and hand phone recordings as data collection tools. The data analysis technique used is qualitative data analysis, researchers use four techniques namely: Data collection analysis, data reduction, data presentation, and conclusion drawdown.